Potential of Borassus Flabellifer Linn Flower Extract as Antidiabetic: An Experimental Study in Alloxan-Induced Hyperglycemic Mice - Ajeng Dian Pertiwi; Afflint Christin Djawa; Wulan Ratia Ratulangi; Tuhfatul Ulya; Haily Liduin Koyou; Musparlin Halid (MEDICA (International Medical Scientific Journal), 2026)
Hyperglycemia resulting from pancreatic β-cell damage remains a major challenge in diabetes mellitus management, highlighting the need for effective bioactive agents to reduce blood glucose levels. This study aimed to assess the antihyperglycemic activity of Borassus flabellifer Linn extract in alloxan-induced mice and to compare the efficacy across different doses. A post-test only control group design was applied with five groups: three treatment groups receiving B. flabellifer extract (200, 400, and 600 mg/kgBW), a positive control, and a negative control (n=5 per group). Blood glucose levels were monitored for seven days after induction and analyzed using one-way ANOVA followed by Tukey HSD post hoc test. All three doses significantly reduced blood glucose levels compared to the negative control (p<0.05). The 600 mg/kgBW dose produced the largest absolute glucose reduction (261.6 mg/dL), while the 200 mg/kgBW dose achieved the best glucose normalization, reaching a final level of 109.4 mg/dL by day 7. These findings highlight a distinction between absolute reduction magnitude and degree of normalization that warrants careful interpretation. Due to the limited sample size (n=5 per group) and short observation period, these results should be considered preliminary. In conclusion, B. flabellifer Linn flower extract demonstrates antihyperglycemic potential across all tested doses. The 200 mg/kgBW dose showed the best glucose normalization, while the 600 mg/kgBW dose produced the largest absolute reduction. These preliminary results support its potential as a natural candidate for antidiabetic therapy and warrant further investigation into its mechanisms, phytochemical profile, and long-term safety.